Gamma spectrometry analysis of radioiodine in charcoal from high volume aerosol samples. (December 2021) - Nolan, L.; Murphy, N.M.; Burbidge, C.I.; O Brien, D.; Leon Vintró, L.; Hanley, O.; Currivan, L.
Abstract: Following accidental releases, gamma spectrometry of impregnated charcoal filters is used to measure gaseous 131 I contamination, but is subject to sampling inhomogeneity. In this study two germanium detectors are calibrated using a charcoal multi-gamma standard. Activities in samples spiked with a matrix of 131 I aliquots are compared based on measurement, spike known activity, and monte-carlo simulation, and used to test a simple mixing method. Measurement efficiency, and removal of 11% inhomogeneity effect by mixing, was successfully reproduced in GESPECOR calculations. Highlights: Development of a simple methodology for the accurate monitoring/measurement of gaseous 131 I in high volume air sampler charcoal filter media is successfully achieved. GESPECOR Monte Carlo simulation software is used to model the measurements.